KARAKTER NAMA TOKOH WAYANG PADA PAPAN NAMA PENANDA GANG DI KOTA PROBOLINGGO: KAJIAN LANSKAP LINGUISTIK PENDEKATAN BUDAYA - Khilmi Mauliddian (tuahtalino, 2019)
This research examines the gang sign board that uses the name of a wayang character as a marker. The purpose of this study was to determine the name of the wayang character and describe the character of the wayang that is on the gang sign board in the Probolinggo city. This study uses a qualitative method using two theoretical approaches namely, Landry and Bourhis Linguistic landscape and the theory of cultural symbols from Bastomi. The data collection techniques in this study used a tool in the form of a photo camera. Data collected in the form of photos containing the writing of the name of the wayang character on the gang sign board and then associated with cultural aspects of the character wayang characters. The results of this study indicate there is one group name namely Pendawa, and five names of wayang figures namely Nakula, Sadewa, Bima, Kresna, and Srikandi. Related to the characters that are owned, the five names of wayang characters have different characters but all of them represent the good side. This research is expected to be useful in exploring language data in a linguistic landscape frame with a cultural approach.